PENGARUH INOKULASI CENDAWAN MIKORIZA ARBUSKULA (CMA) DAN BERBAGAI TARAF PUPUK P TERHADAP KADAR P DAUN DAN KUALITAS BmIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PEMBIBITAN PENDAHULUAN - Eko Sulistyono; M. H. Bintoro Djoefrie; Ismantiri Heningtyas (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1999)
Glasshouse experiment was conducted to study the effect of mycorrhizae inoculation and it's interaction with P supply on P leaf content and quality of oil palm seedling. Factorial experiment was arranged in Randomized Block Design with three replications. The first factor were mycorrhizae inoculation : without inoculation, mixed mycorrhizae, Acaulospora sp, Glomus manihotis, Glomus sp.1, Glomus sp. 2, Glomus sp. 3, The second factor were level of Roch Phosphate fertilizer : 0 g/seedling, 2 g/seedling, 4 g/seedling and 6 g/seedling. Mycorrhizae inoculation affected the P leaf content and percentage of infection significantly, Glomus sp decreased P leaf content. Acaulospora sp. gave the best quality of seedling, but Glomus sp. 3 gave the bad one. The Rock Phosphate application did not affect on P leaf content absorption efficiency and inoculation percentage due to high soil phosphorus content.